Electrocaloric Response of Ferroelectric Material Applicable as Electrothermal Transducer - Saber Mohammadi; Akram Khodayari; Arash Ahmadi (Advances in Materials Science and Engineering)
Electrocaloric response of the PMN-10PT is measured experimentally and compared with the numerical results. Based on the compatibility of the experimental and numerical results, feasibility of using ferroelectric materials as an electrothermal transducer has been investigated. In this study, electrocaloric response of three different ferroelectric capacitors (PMN-10PT, PMN-25PT, and PZN-4.5PT) under an applied periodic electric field have been investigated. Alternative switching of the electrocaloric elements with specific boundary conditions generates a directed heat flux. It can be concluded that each ferroelectric material can be used as a transducer in a special temperature range that in which it has good electrocaloric response.